Blue carbon stocks, accumulation rates, and associated spatial variability in Brazilian mangroves. Issue 2 (12th October 2020) - Hatje, Vanessa; Masqué, Pere; Patire, Vinicus F.; Dórea, Antonio; Barros, Francisco
Abstract: We assessed the influence of the intertidal and salinity gradients and mangrove forest structure on C stocks and sequestration rates in mangrove soils of an estuarine system in Todos os Santos Bay, Eastern Brazil. The accumulation rates of organic C (Corg ) during the last century varied between and within estuarine zones, ranging from 65 to 1073 g Corg m −2 yr −1 . The mean stocks of Corg and N for the top 1 m soils were 263 ± 14 Mg Corg ha −1 and 11.8 ± 0.4 Mg N ha −1, respectively. We found a less variable distribution pattern on Corg and N stocks throughout the salinity gradient than along the intertidal gradient, being significantly higher at the fringe mangroves than at the interior forest. We estimated that Brazil, one of the major reservoirs of mangroves (~ 10%) on the planet, has 207 ± 34 Tg Corg in the upper meter of soils, which represents 3–8% of the C stored in mangrove soils globally. Given that Brazil is a Blue Carbon hotspot, it is emphasized the urgent need for the establishment of better mangrove conservation practices and a comprehensive evaluation of their value in climate change mitigation and adaptation strategies for reducing CO2 emissions.